2019
DOI: 10.1039/c9cy00351g
|View full text |Cite
|
Sign up to set email alerts
|

An efficient bifunctional electrocatalyst based on a nickel iron layered double hydroxide functionalized Co3O4 core shell structure in alkaline media

Abstract: An electrocatalyst based on a nickel iron layered double hydroxide functionalized Co3O4 core shell structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 55 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…S3d and e †). It should be noted that, due to the formation of oxide/nitride heterostructures with abundant interfaces, the overpotential at 10 mA cm À2 of Co 4 N-Co 3 O 4 -C/CC-5 electrode prepared via plasma treatment of MOF is superior to most of the MOFs-derived Cobased oxide electrocatalysts in the alkaline solution reported thus far, e.g., Co 3 O 4 (303 mV), 48 V O -Co 3 O 4 (300 mV), 47 Co-Ni 3 N nanorods (194 mV), 44 Co(OH) 2 @NCNTs@NF (170 mV), 45 Co 4 N@NF (112 mV), 49 Co@NG (200 mV), 43 and Co@N-CNTs@rGO. 50…”
Section: Synthesis and Characterization Of Co 4 N-co 3 O 4 -C/ccmentioning
confidence: 96%
See 1 more Smart Citation
“…S3d and e †). It should be noted that, due to the formation of oxide/nitride heterostructures with abundant interfaces, the overpotential at 10 mA cm À2 of Co 4 N-Co 3 O 4 -C/CC-5 electrode prepared via plasma treatment of MOF is superior to most of the MOFs-derived Cobased oxide electrocatalysts in the alkaline solution reported thus far, e.g., Co 3 O 4 (303 mV), 48 V O -Co 3 O 4 (300 mV), 47 Co-Ni 3 N nanorods (194 mV), 44 Co(OH) 2 @NCNTs@NF (170 mV), 45 Co 4 N@NF (112 mV), 49 Co@NG (200 mV), 43 and Co@N-CNTs@rGO. 50…”
Section: Synthesis and Characterization Of Co 4 N-co 3 O 4 -C/ccmentioning
confidence: 96%
“…(e) The linear fitting of the capacitive currents of the electrodes as a function of scan rates for ZIF-67 and Co 4 N-Co 3 O 4 -C/CCs prepared with different plasma treatment times. (f) The chronopotentiometry curve of Co 4 N-Co 3 O 4 -C/CC-5 was recorded at 20 mA cm À2 for a total duration of 140 h. (g) A comparison of the overpotentials at 10 mA cm À2 of Co 4 N-Co 3 O 4 -C/CC-5 and reported cobaltbased catalysts 20,21,[42][43][44][45][46][47][48][49][50][51].…”
mentioning
confidence: 99%
“…Different methods have been adopted for the immobilization of various nano-and microstructured materials on FTO, such as hydrothermal, solvothermal, and electrochemical deposition. [251][252][253][254] For example, Bogdanoff et al [251] reported on α-Mn 2 O 3 electrodes prepared by galvanostatic deposition of MnOOH x films with a varied thickness on a conductive FTO glass substrate, followed by annealing for 1 h under air at 773 K. The as-synthesized α-Mn 2 O 3 was found to have a large electrochemical active surface area and good electrical conductivity. In addition, a unique, robust, and highly efficient bifunctional nickel phosphite (Ni 11 (HPO 3 ) 8 (OH) 6 ) electrocatalyst with excellent structural features has been electrophoretically deposited on FTO for water splitting.…”
Section: Fluorine-doped Tin Oxide (Fto)mentioning
confidence: 99%
“…Figure 5f shows the better HER activity of the CMO-U@CC electrode compared with those of other reported oxide-based electrocatalysts. [70,78,[85][86][87][90][91][92][93][94][95][96][97][98][99] After the HER process, the CMO-U@CC electrode was analyzed via XPS, XRD, and FESEM. The XPS results (Figure S11a-c, Supporting Information) revealed the compositional changes on the surface of the electrocatalyst after the electrocatalytic HER.…”
Section: Her Electrocatalytic Activitymentioning
confidence: 99%